The influence of governance quality factors on stock market performance in ASEAN / Liyana Syafini Jumaah ... [et al.] - Jumaah, Liyana Syafini; Bahrudin, Nur Zahidah; Muda, Ruhaini; Sahudin, Zahariah; Abdullah, Hasni (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2023)
Whilst regional participation across ASEAN induces the liberalization of trade and investment, as well as other forms of economic cooperation, the quality of governance plays a crucial role as it is a key component of sustainability. This study aimed to examine how governance quality factors influenced stock market performance. This study applied the Panel Least Square (PLS) and Panel Cointegration Full-Modified Ordinary Least Squares (FMOLS) estimations to gauge how quality governance factors impact an integrated ASEAN stock market in the long run. This study utilized data from the ASEAN Exchanges covering the period 2002 to 2020. The findings demonstrated the significant positive influence of voice and accountability, as well as political stability and the lack of violence; meanwhile, rule of law negatively affects the stock market performance. The study also identified a long-term relationship between governance quality and stock market performance. This implies that higher-quality governance improves the stock market performance in an integrated market.